Additions to the genus Lessingianthus (Asteraceae, Vernonieae) from South America - Dematteis, Massimiliano (2010)
Two new species of Lessingianthus (Asteraceae: Vernonieae) are described and illustrated. One of these L. Foliosus Dematt., bears a resemblance to L. Vepretorum, but can be separated from it by its linear leaves, that are lanate on the abaxial surface, and by its shorter internodes. The other new species, L. Lapinhensis Dematt. Can be easily separated from L. Brevifolius and other taxa of the genus by the combination of stems 8-18 cm tall, glabrous linear leaves and campanulate involucres. Thirteen other taxa previously described as Vernonia are transferred to the genus Lessingianthus and two lectotypes are designated here.